How do transnational grassroots networks reframe the global norms of water and forests governance? - Émilie Dupuits; Géraldine Pflieger (Développement Durable et Territoires)
The current era of globalization and commodification has had a substantial impact on common-pool resources governance. In direct response to this, community-based organizations managing water and forests at the local level began to create their own transnational networks. Primarily, these organizations aim to achieve direct representation in international decision-making arenas in order to promote their model of collective governance. By reframing the representations of common-pool resources (from commodities to human rights or collective goods), they seek to influence norm-building processes and establish specific scales of community-based governance (local, regional or global).To what extent does the reframing of common-pool resources impact the scales of water and forests governance? This paper addresses the question by adopting a geographical approach of transnational social movements and undertaking a discourse analysis. The study focuses on two case studies: the Latin-American Confederation of Community Organizations for Water Services and Sanitation (CLOCSAS), and the Mesoamerican Alliance of Peoples and Forests (AMPB). On one hand, CLOCSAS frames water as a global common good and a universal human right compatible with an economic value. It aims to become an alternative expert on water issues. On the other hand, AMPB frames forests as a local common good and a territorial right. It aims to be differentiated from technical experts and works to consolidate territorial authority.